Cocoa agroforestry is less resilient to sub-optimal and extreme climate than cocoa in full sun - Abdulai, I.; Vaast, Philippe; Hoffmann, M.P.; Asare, R.; Jassogne, Laurence T.P.; Asten, Piet J.A. van; Rötter, Reimund P.; Graefe, Sophie (Wiley, 2018)
Cocoa agroforestry is perceived as potential adaptation strategy to sub-optimal or adverse environmental conditions such as drought. We tested this strategy over wet, dry and extremely dry periods comparing cocoa in full sun with agroforestry systems: shaded by (i) a leguminous tree species, Albizia ferruginea and (ii) Antiaris toxicaria, the most common shade tree species in the region. We monitored micro-climate, sap flux density, throughfall, and soil water content from November 2014 to March 2016 at the forest-savannah transition zone of Ghana with climate and drought events during the study period serving as proxy for projected future climatic conditions in marginal cocoa cultivation areas of West Africa. Combined transpiration of cocoa and shade trees was significantly higher than cocoa in full sun during wet and dry periods. During wet period, transpiration rate of cocoa plants shaded by A. ferruginea was significantly lower than cocoa under A. toxicaria and full sun. During the extreme drought of 2015/16, all cocoa plants under A. ferruginea died. Cocoa plants under A. toxicaria suffered 77% mortality and massive stress with significantly reduced sap flux density of 115 g cm−2 day−1, whereas cocoa in full sun maintained higher sap flux density of 170 g cm−2 day−1. Moreover, cocoa sap flux recovery after the extreme drought was significantly higher in full sun (163 g cm−2 day−1) than under A. toxicaria (37 g cm−2 day−1). Soil water content in full sun was higher than in shaded systems suggesting that cocoa mortality in the shaded systems was linked to strong competition for soil water. The present results have major implications for cocoa cultivation under climate change. Promoting shade cocoa agroforestry as drought resilient system especially under climate change needs to be carefully reconsidered as shade tree species such as the recommended leguminous A. ferruginea constitute major risk to cocoa functioning under extended severe drought.